2020
DOI: 10.1159/000506757
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Agreement for the International Academy of Cytology Yokohama System for Reporting Breast Fine-Needle Aspiration Biopsy Cytopathology

Abstract: Background: A number of guidelines have been developed to improve standardization of the terminology and criteria for cytologic specimens obtained from the thyroid, pancreas, lung, and salivary glands. A major goal of these guidelines is to improve reproducibility and understanding of the reporting of diagnostic results among cytopathologists and between cytopathologists and clinicians. The International Academy of Cytology Yokohama System for Reporting Breast Fine-Needle Aspiration Biopsy Cytopathology (IAC Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
2
17
0
1
Order By: Relevance
“…Overall, interobserver agreement has ranged from fair to good when analyzed by calculating observed agreement, chance-corrected agreement (kappa), chance-corrected weighted agreement (weighted kappa). [8][9][10][11][12][13][14] In our study of the TIS, overall observed agreement was 68% with a chance-corrected agreement (kappa) of 51% and weighted kappa was 0.63. The chance-corrected value (kappa) and weighted kappa fall within the range of prior studies for interobserver agreement at other sites (Table 5).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Overall, interobserver agreement has ranged from fair to good when analyzed by calculating observed agreement, chance-corrected agreement (kappa), chance-corrected weighted agreement (weighted kappa). [8][9][10][11][12][13][14] In our study of the TIS, overall observed agreement was 68% with a chance-corrected agreement (kappa) of 51% and weighted kappa was 0.63. The chance-corrected value (kappa) and weighted kappa fall within the range of prior studies for interobserver agreement at other sites (Table 5).…”
Section: Discussionmentioning
confidence: 54%
“…However, such a distribution of cases is substantially similar to other interobserver reproducibility studies reported in the literature. [8][9][10][11][12][13][14][15] Finally, the study has only three raters for the cases. This number of cytopathologist raters is not dissimilar to other studies published in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Very similar results ranging from only fair to moderate agreement between observers was reported for other organs, including cytological diagnoses. For example, in the fine-needle aspirations of salivary glands and breast, the overall κ-values have been reported to be 0.314 and 0.50 and the variation of values, respectively, from 0.091 to 0.539 and from 0.41 to 0.62 [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…Para complementar, el sistema internacional Yokohama también aporta algoritmos de conducta clínica para cada categoría de diagnóstico, la utilidad de las pruebas especiales como la inmunocitoquímica en bloque celular y de biología molecular en la subclasificación de la patología mamaria maligna, así como el uso de la citología en base líquida en muestras citológicas mamarias, para optimizar la evaluación multidisciplinaria de la patología mamaria y su tratamiento [2,7].…”
Section: Malignaunclassified